Pericentromeric Duplications in the Laboratory Mouse - Thomas, James W.; Schueler, Mary G.; Summers, Tyrone J.; Blakesley, Robert W.; McDowell, Jennifer C.; Thomas, Pamela J.; Idol, Jacquelyn R.; Maduro, Valerie V.B.; Lee-Lin, Shih-Queen; Touchman, Jeffrey W.; Bouffard, Gerard G.; Beckstrom-Sternberg, Stephen M.; et al. (Genome Research, 2003)
Duplications have long been postulated to be an important mechanism by which genomes evolve. Interspecies genomic comparisons are one method by which the origin and molecular mechanism of duplications can be inferred. By comparative mapping in human, mouse, and rat, we previously found evidence for a recent chromosome-fission event that occurred in the mouse lineage. Cytogenetic mapping revealed that the genomic segments flanking the fission site appeared to be duplicated, with copies residing near the centromere of multiple mouse chromosomes. Here we report the mapping and sequencing of the regions of mouse chromosomes 5 and 6 involved in this chromosome-fission event as well as the results of comparative sequence analysis with the orthologous human and rat genomic regions. Our data indicate that the duplications associated with mouse chromosomes 5 and 6 are recent and that the resulting duplicated segments share significant sequence similarity with a series of regions near the centromeres of the mouse chromosomes previously identified by cytogenetic mapping. We also identified pericentromeric duplicated segments shared between mouse chromosomes 5 and 1. Finally, novel mouse satellite sequences as well as putative chimeric transcripts were found to be associated with the duplicated segments. Together, these findings demonstrate that pericentromeric duplications are not restricted to primates and may be a common mechanism for genome evolution in mammals.[Supplemental material is available online at www.genome.org.]
10.1101/gr.791403